ANALYZING THE IMPACT OF PT PELINDO'S PERFORMANCE AFTER THE MERGER (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
Indonesia is the largest archipelago in the world with a long maritime history, of course it has many ports as a means to improve the Indonesian economy, especially in the maritime sector. Therefore, Pelabuhan Indonesia (Pelindo) was formed, where Pelabuhan Indonesia (Pelindo) is a world-class port that offers integrated services between ports in Indonesia. Pelindo is a company formed from the merger of four national port companies, namely PT Pelindo I (Persero), PT Pelindo II (Persero), PT Pelindo III (Persero) and PT Pelindo IV (Persero). It was established on October 1, 2021. Pelindo became an integrated company due to the strategic initiative of the government as a shareholder to realize national connectivity and a stronger logistics ecosystem network. Maritime connectivity enhances connectivity between domestic and foreign ports. One of the best ways to strengthen the company's foundation in accordance with its legal constitution is through a merger. The merger strategy is expected to accelerate the company in achieving its goals. The decision to merge Pelindo is a step to improve access to global markets and technology, achieve operational efficiency, encourage innovation, share resources and reduce domestic logistics costs. After the merger of Pelindo, there is a perceived impact such as increased efficiency and productivity in operational performance.